An exploratory study on the teaching and learning at post-listening stage by International Standard Program students, ULIS-VNU - Bùi, Thị Hằng (University of Languages and International Studies, 2017)
The recent education reform, most obviously in ELT has brought a new identity to the teaching procedure of language skills, comprising three stages: Pre, While and Post stage. However, the importance of the post stage tends to be lowered as the optional pa (...)